Remittances, institutions and financial inclusion: new evidence of non-linearity - Issabayev, Murat; Saydaliyev, Hayotbek; Avsar, Veysel; Lee, Chin (World Scientific, 2020)
This paper investigates the effect of remittance inflows on financial inclusion. Using data from high remittance-receiving developing countries and applying dynamic panel data methods, we find that remittance inflow has a negative impact on financial inclusion for countries with low level of remittances. However, this relationship is positive for countries with high level of remittances. Our study found that there exists a nonlinear relationship between remittances and financial inclusion. We also show that the effect of remittances on the financial inclusion is conditional upon people’s perception about institutions.